TINGKAT MOTIVASI KERJA DAN IKLIM ORGANISASI DALAM MENINGKATKAN KINERJA GURU DI SD NEGERI GUGUS GARUT KECAMATAN DARUL IMARAH ACEH BESAR - Budi Artina; Rita Novita; Sariakin (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This research aims to investigate the extent to which work motivation and organizational climate contribute to improving teacher performance at SD Negeri Gugus Garut, Darul Imarah District, Aceh Besar. This study employs a quantitative approach with a correlational design. The population consists of all primary school teachers in the cluster, and a proportional random sample of 36 teachers was selected. Data were collected through questionnaires and analyzed using multiple linear regression. The study found that work motivation and organizational climate together have a positive and significant impact on teacher performance in this school. This indicates that both work motivation and organizational climate play crucial roles in enhancing teacher performance. In other words, higher work motivation and a conducive organizational climate lead to better performance among teachers at SD Negeri Gugus Garut. In light of these findings, schools should enhance factors influencing teacher work motivation and organizational climate. Concrete steps include conducting training programs for professional development to enhance motivation and job satisfaction. Moreover, improving communication among staff and recognizing contributions can foster a supportive organizational climate, potentially enhancing overall teacher performance. Investing in improving work motivation and organizational climate thus emerges as an effective strategy to enhance educational quality in schools.